The Best Location for Speed Bump Installation Using Experimental Design Methodology - Khademi, Alireza; Ghorbani Renani, Nafiseh; Mofarrahi, Maryam; Rangraz Jeddi, Alireza; Mohd Yusof, Noordin (Promet - Traffic&Transportation, 2013)
Speed bumps, as traffic calming devices, have been extensively used to reduce traffic speed on local streets. This study represents a unique application of experimental design methodology where the effects of some controllable factors in determining the best location for installing speed bumps before stop points (e.g. entry gates, road junctions) were investigated. Through Classical Design of Experiments (DOE), the optimum location of the speed bump was obtained based on the graphical plots of the significant effects. The speed at the stop point was treated as the response and minimum speed is desirable. Design-Expert® software was used to evaluate and analyze the results obtained. The suggested mathematical model effectively explains the performance indicators within the ranges of the factors. The car speed is the most significant factor that affects the distance-time in comparison with other factors, which provides secondary contributions.